2021
DOI: 10.1016/j.kint.2020.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear antigen–reactive CD4+ T cells expand in active systemic lupus erythematosus, produce effector cytokines, and invade the kidneys

Abstract: Systemic lupus erythematosus is a systemic and chronic autoimmune disease characterized by loss of tolerance towards nuclear antigens with autoreactive CD4 D T cells implicated in disease pathogenesis. However, very little is known about their receptor specificity since the detection of human autoantigen specific CD4 D T cells has been extremely challenging. Here we present an analysis of CD4 D T cells reactive to nuclear antigens using two complementary methods: T cell libraries and antigenreactive T cell enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…This is comparable with past study demonstrating that untreated SLE patients had higher surface levels of gp130 on CD4 + T cells than inactive or stable SLE patients (47). Subsets of CD3 + CD4 + cells have been shown to be expanded in active SLE (48,49), and overactive or chronically active T cells are crucial in the pathogenesis of SLE (50,51). In addition, correlation with SLEDAI-2K scores was not observed in our cohort of patients when surface levels of IL-12Rb2 were taken into account i.e.…”
Section: Discussionsupporting
confidence: 90%
“…This is comparable with past study demonstrating that untreated SLE patients had higher surface levels of gp130 on CD4 + T cells than inactive or stable SLE patients (47). Subsets of CD3 + CD4 + cells have been shown to be expanded in active SLE (48,49), and overactive or chronically active T cells are crucial in the pathogenesis of SLE (50,51). In addition, correlation with SLEDAI-2K scores was not observed in our cohort of patients when surface levels of IL-12Rb2 were taken into account i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Given the potential contribution of a SLE associated hyperresponsiveness, cells were also stimulated with the control antigen TTR and no differences in reactive cell numbers were detected. Using the same experimental set-up, previous work from our group also found no differences between active and inactive SLE patients and healthy controls upon stimulation with the recall antigen MP65 from candida albicans 31 .…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, CD103+ TRM cells in the skin are positively correlated to disease severity and recurrence in patients. While TRM and T cell antigen specificities in lupus nephritis were recently described ( 52 , 53 ), specificities of skin autoreactive T cells are unknown. A trial blocking anti-IL-17 antibody for DLE is recruiting (NCT03866317).…”
Section: Trm In Vitiligomentioning
confidence: 99%
“…The T cell specificities in CLE skin are largely unknown, but SLE studies identified T cells reactive to nucleosomes/histones ( 59 ), which can induce anti-dsDNA antibody production ( 60 ). A recent study characterized antigen specificities of T cells in the kidney in lupus nephritis patients, and found that they recognize SmD1, RNP70, histone, Ro, La, and nuclear antigen ( 52 , 61 ). A population of CD8+ CD103+ tissue-resident memory T cells was identified and correlated positively with disease severity in patients ( 53 ).…”
Section: Trm In Cutaneous Lupus Erythematosusmentioning
confidence: 99%